Chitosan conjugation enables intracellular bacteria susceptible to aminoglycoside antibiotic. (14th November 2016) - Mu, Haibo; Niu, Hong; Wang, Dongdong; Sun, Feifei; Sun, Yuelin; Duan, Jinyou
Abstract: Most chronic infections are difficult to eradicate because bacteria capable of surviving in host-infected cells may be protected from the killing actions of antibiotics, leading to therapy failures and disease relapses. Here we demonstrated that covalent-coupling chitosan to streptomycin significantly improved intracellular bactericidal capacity towards multiple organisms within phagocytic or nonphagocytic cells. Structure–activity relationship investigations indicated that antibiotic contents, molecular size and positive charges of the conjugate were the key to retain this intracellular bactericidal activity. Mechanistic insight demonstrated the conjugate was capable to target and eliminate endocytic or endosomal escaped bacteria through facilitating the direct contact between the antibiotic and intracellular organism. In vivo acute infection models indicated that compared to equal dose of the antibiotic, chitosan-streptomycin (C-S) conjugate and especially the human serum album binding chitosan-streptomycin conjugate (HCS) complex formed by human serum album and C-S conjugate greatly decreased the bacteria burden in the spleen and liver in both wild type and immuno-suppressive mice. Furthermore, the HCS complex remarkably reduced mortality of infected TLR2 deficient mice, mimicking immune-compromised persons who were more susceptible to bacterial infections. These findings might open up a new avenue to combat intracellular bacterial infection by aminoglycosides antibiotics at a lower effective dose.